Telaah Akad Dalam Tradisi Ombengan; Perspektif Kaidah Al-‘Adah Al-Muhakkamah - M Hibatullah Huwaidi (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to find the meaning and pattern of the ombengan tradition in Karanganyar village, Paiton sub-district, Probolinggo district, then look at the terms of the contract based on the rules of al-'adah al-muhakkamah. The approach used in this study is ethnographic which aims to explore the meaning and patterns of the ombengan tradition that prevails in this village community. The result of this research is that ombengan is categorized as debt if the nominal is more than 100 thousand and becomes a grant if it is less than that nominal. And this tradition is in accordance with the rules of al-'adah al-muhakkamah so that it can be used as a basis for sharia law.